Illumination removal and text segmnetation for Al-Quran using binary representation - Nazeeh Jamil Bany Melhem (2015)
Segmentation process for segmenting Al-Quran needs to be studied carefully. This is because Al-Quran is the book of Allah swt. Any incorrect segmentation will affect the holiness of Al-Quran. A major difficulty is the appearance of illumination around text areas as well as of noisy black stripes. In this study, we propose a novel algorithm for detecting the illumination on Al-Quran page. Our aim is to segment Al-Quran pages to pages without illumination, and to segment Al-Quran pages to text line images without any changes on the content. First we apply a pre-processing which includes binarization. Then, we detect the illumination of Al-Quran pages. In this stage, we introduce the vertical and horizontal white percentages which have been proved efficient for detecting the illumination. Finally, the new images are segmented to text line. The experimental results on several Al-Quran pages from different Al-Quran style demonstrate the effectiveness of the proposed technique.